Are systolic velocity duplex metrics negatively affected by flow aliasing in areas of critical internal carotid artery stenosis - Artem Shmelev; Ghaleb Darwazeh; Avinash Ganti; Motahar Hosseini; Amanda Beneat; Donald Wilkerson; Shelby Wilkerson; Michael Zatina (Greater Baltimore Medical Center, 2019)
Purpose: Duplex scanning is a useful noninvasive screening tool for the detection of carotid bifurcation disease. Internal carotid artery (ICA) peak systolic velocity (PSV) and ICA/common carotid artery (CCA) PSV ratios are proven metrics determining 70%-99% ICA stenosis. A potential disadvantage of using dramatically increasing systolic velocity measurements in areas of critical arterial stenosis is flow aliasing. Diastolic velocity should be less influenced by this flow artifact. We evaluate ICA and CCA end diastolic velocity (EDV) metrics in predicting severe ICA stenosis and document the prevalence of an aliasing artifact in a population of patients with critical ICA stenosis. Methods: Consecutive patients undergoing carotid duplex assessments and contrast angiography were compared (n = 140). ICA and CCA PSV and EDV were recorded as was evidence of the flow aliasing of ICA waveforms. ICA/CCA PSV and EDV ratios were calculated. Duplex parameters were compared with angiographic ICA measurements. Receiver-operator characteristic curve (ROC) analysis was used to determine optimal criteria to identify ICA stenosis of 70% to 99%. Results: Of 256 carotid bifurcation duplex studies, critical angiographic stenosis was present in 105 arteries. Only four completed arterial duplex scans demonstrated flow aliasing. In three of these patients, systolic metrics were non-diagnostic versus ICA/CCA EDV ratios. An ICA/CCA EDV ratio of 2.3 provided the best combination of sensitivity 73.8% and specificity 75.18%. Conclusion: ICA/CCA diastolic ratios reliably determine 70% or greater ICA stenosis. Flow aliasing infrequently complicates ICA PSV.